The Success of the Nordic Countries as a Blueprint for Small Open Economies - Johannes Tiemer (Intereconomics, 2018)
To retain their leading position, the Nordics must invest in developing more sophisticated products than competing economies like Turkey. This applies to all complex economies, but constitutes a greater challenge to the Nordic countries with their comparatively small populations.
Keywords: 330